3D porous nano Co3O4/C composite catalyst for the thermal decomposition of ammonium perchlorate. (December 2022) - Wen, Tao; Feng, Yang; Bi, Yuqiang; Xu, Liang; Guo, Changping
Abstract: In this work, nano Co3 O4 /C composite catalyst was in-situ synthesized on sponge by high-temperature calcination, and as a catalyst for the thermal decomposition of AP. SEM, EDS, XRD and BET analyses showed that the prepared samples were evenly distributed and nano-sized Co3 O4 /C composites. Moreover, the catalytic effect of the nanocomposite catalyst on the thermal decomposition of AP was studied by DSC and TG. The influence of different factors on the thermal decomposition performance of AP were studied. The results indicated that when the Co3 O4 /C composite catalyst content was 5 wt%, the high-temperature decomposition (HTD) peak of AP was reduced from 430.1 to 319.0 ℃ and the activation energy from 237.5 down to 81.1 kJ mol −1 . In addition, the possible catalytic mechanism was also briefly discussed. Therefore, all the results indicated that the 3D porous nano Co3 O4 /C composite catalyst demonstrated excellent catalytic performance for the thermal decomposition of AP. Graphical Abstract: ga1 Highlights: Nano Co3 O4 /C composite catalysts ware synthesized by high-temperature calcination method. Co3 O4 nanoparticles were synthesized in situ on spone and uniformly dispersed in its 3D porous networks. Nano Co3 O4 /C composite catalysts could effectively reduce HTD temperature and activation energy of AP. A possible catalytic mechanism was proposed.